2020
DOI: 10.14744/ejmo.2020.36102
|View full text |Cite
|
Sign up to set email alerts
|

IN Silico Approach of Some Selected Honey Constituents as SARS-CoV-2 Main Protease (COVID-19) Inhibitors

Abstract: The huge attack of coronavirus disease 2019 (COVID-19) over all the world forces the researcher around the world to study the crystal structure of the main protease M pro (3-chymotrypsin-like cysteine enzyme) which is the essential enzyme for coronavirus processing the polyproteins and its life cycles. And by the way, the inhibition of this enzyme active site becomes the target of all scientists of drug discovery in order to overcome this disease. In this study, we have used the molecular modeling approach to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 20 publications
0
38
0
1
Order By: Relevance
“…On April 13, 2020, an exciting preprint was posted on ChemRxiv by Heba Hashem, where the author had conducted an in silico analysis (molecular docking) to assess the potential effects of natural phenolic chemical compounds from honey against SARS-COV-2 [ 105 ]. Heba suggested that caffeic acid, caffeic acid phenethyl ester (CAPE), galangin, and chrysin have good potential to inhibit the viral 3-chymotrypsin-like cysteine protease (3CL pro ) enzyme, and thus inhibit viral replication [ 105 ]. The overall concept of this hypothesis is extensively explained in Figure 7 .…”
Section: Promising Insights For Honey Research Amid Covid-19 Outbrmentioning
confidence: 99%
“…On April 13, 2020, an exciting preprint was posted on ChemRxiv by Heba Hashem, where the author had conducted an in silico analysis (molecular docking) to assess the potential effects of natural phenolic chemical compounds from honey against SARS-COV-2 [ 105 ]. Heba suggested that caffeic acid, caffeic acid phenethyl ester (CAPE), galangin, and chrysin have good potential to inhibit the viral 3-chymotrypsin-like cysteine protease (3CL pro ) enzyme, and thus inhibit viral replication [ 105 ]. The overall concept of this hypothesis is extensively explained in Figure 7 .…”
Section: Promising Insights For Honey Research Amid Covid-19 Outbrmentioning
confidence: 99%
“…Honey has anti-bacterial properties thanks to its content of phenolic compounds, the production of hydrogen peroxide and other mechanisms such as osmosis [173]. Moreover, it has been suggested to have a role against COVID-19 epidemic [174,175], it has six compounds with affinity with the receptor active site of COVID-19 main protease according to a in silico approach [176] and is currently being tested in a clinical trial (clinical trial NCT04323345) [176]. It is noted that honey displays anti-thrombotic activity [177] and it especially acts as a PAF inhibitor [178].…”
Section: Honeymentioning
confidence: 99%
“…Interestingly, honeybee products have been used in treatment of many diseases including tumor and immune-related diseases ( Yusuf et al, 2007 ; Wieckiewicz et al, 2013 ). In this regard, honey, propolis, Bee pollen and Bee venom created by bees possess many biological activities like antibiotic, antifungal, antioxidant, antiviral, inhibitor, anti-cancer, and immunomodulatory, hepatoprotective effects ( Banskota et al, 2001 ; Tolba et al, 2013 ; Pasupuleti et al, 2017 ; Hashem, 2020 ; Shaldam et al, 2020 ). The following sections include an overview about structure, pathogenesis and mechanistic activities of SARS-CoV-2 and the potential application of Bee’s products in treatment of the disease.…”
Section: Introductionmentioning
confidence: 99%